Diseño e implementación de un módulo didáctico con HMI para controlar el sistema de refrigeración en el laboratorio de aire acondicionado en la Universidad Técnica de Cotopaxi extensión La Maná, año 2015 - Pilaguano Orovio, Edison Reinaldo (2016)
This titling project aims to design and implement a training module with HMI to control the cooling system at the Laboratory of Air Conditioning Electromechanics Engineering. At present industrial processes are still handled manually, which is not beneficial to increase production, since the processes are increasingly complex and require the presence of the operator for quality control. Automation is the replacement of human labor by computer and electromagnetic systems therefore, processes to be controlled by an HMI.